The influence of gamification features, user experience, and e-service quality on Shopee's repurchase intention - Rikka Pratiwi Walga; Yuliza Betty Harleni (Institute of Computer Science (IOCS), 2026)
The fast growth of e-commerce is making it harder for online marketplaces to keep customers and get them to buy again. Shopee, one of the biggest e-commerce platforms in Indonesia, uses different digital strategies like gamification, improving user experience, and offering good electronic service quality to make customers happier. This study looks at how gamification, user experience, and e-service quality affect the desire to buy again, with customer satisfaction playing a key role in between. The research uses a quantitative method called Structural Equation Modeling – Partial Least Squares (SEM-PLS). Data was gathered from 300 Shopee users in five major cities in Indonesia: Jakarta, Surabaya, Bandung, Medan, and Palembang. The results show that gamification, user experience, and e-service quality all have a positive and significant effect on customer satisfaction. Moreover, customer satisfaction has a positive and significant effect on the intention to buy again and serves as a mediator between the main factors and repurchase intention. These findings highlight the importance of improving user experience and digital service quality to boost customer satisfaction and loyalty on e-commerce platforms